Essential Oil of Alpinia galanga: Effect of Aromatherapy Inhalation in Mice and Physicochemical Characterization - Ni Made Dwi Mara Widyani Nayaka; Ni Luh Putu Swari; Putu Era Sandhi Kusuma Yuda; I Gusti Ayu Agung Kusuma Wardani (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2022)
Aromatherapy has been used for centuries to maintain body and mental health. In aromatherapy, the inhalation of essential oil provides physical and psychological benefit due to its volatile bioactive compounds. The current study was aimed to determine the effect of the inhalation of Alpinia galanga essential oil in mice using forced swim test. The refractive index, solubility, and Gas Chromatography-Mass Spectrophotometry (GC-MS) profile of AGEO were also investigated. The essential oil from Alpinia galanga showed an anti-depressive-like effect and it was as strong as the positive control (Lavandula angustifolia essential oil). The GC-MS analysis discovered some antidepressant compounds in the oil such as eucalyptol, fenchone, and α-terpineol.